(untitled) - Wilt, Timothy (Great Britain, 2003)
This book offers a broad-based, contemporary perspective on Bible translation in terms of academic areas foundational to the endeavor: translation studies, communication theory, linguistics, cultural studies, biblical studies and literary and rhetorical studies. The discussion of each area is geared towards non-specialists, to introduce them to notions, trends and tools that can contribute to their understanding of translation. The Bible translator is encouraged to appreciate various approaches to translation in view of the wide variety of communicative, organizational and sociocultural.
Keywords: Wilt, Timothy